Perkembangan Pendidikan Islam di Indonesia dan Upaya Penguatannya dalam Sistem Pendidikan Nasional - Miftahul Huda (Journal of Islamic Education Research, 2020)
This paper aims to analyze the development of Islamic education in Indonesia and efforts to strengthen it in the national education system. This type of research is descriptive qualitative. Study of literature by focusing on terms of peeling, summarizing and collecting a literature, then the authors provide an analysis of the data that has been collected. The results showed that during the pre-independence era religious education was not only not recognized but also not included in the education system, it was even suspected of being a place to incite and fight the invaders. At the time of independence it did not yet have a role because the government still tended to be controlled by nationalist and secular groups, if there were Islamic groups, Islam was still more abangan. Thus the New Order government continuously fostered the quality of madrasa education so that in 1975 a joint decree (SKB) was issued by three ministers on Improving the Quality of Education in Madrasas, where the SKB of the three ministers had advantages and disadvantages. So that the solution of this weakness is the government is trying to make breakthroughs to restore the function of the madrasa as a place to print religious leaders, namely by opening an alternative Madrasah Aliyah named Madrasah Aliyah Special Program (MAPK). Henceforth, this MAPK was changed to Madrasah Aliyah Religious (MAK) which focuses and strengthens the field of Islamic education. There are two strengthening of Islamic education in the national education system, namely strengthening Islamic educational institutions, and strengthening religious subjects in all schools both under the auspices of the Ministry of Religion and other Ministries.